THE QUESTIONS OF QUALITY OF LIFE AFTER OPERATIONS FOR THE BREAST CANCER - V. V. Maslyakov; T. V. Smirnova; E. N. Nakaeva (Современная наука и инновации)
The article made assessment of the quality of life of patients after surgery for malignant tumors of the breast. For this purpose it was performed a survey of230 female patients who are on dispensary observation by an oncologist at the place of residence. All the patients had cancer stages Tl-2N0-xT0. All the patients in the anamnesis was performed surgery in the period from 1 year to 5 years, further treatment included the implementation mastectomy, chemo, radiotherapy that was conducted in the first year after surgery